Navigating resistance on digital platforms: delivery and transportation labor in Türkiye - Ersöz, Batuhan; Başaran, Altan (Frontiers in Sociology, 2024)
Digital platforms are transforming the world of work. However, platforms operating in similar fields of activity encounter varying mechanisms of opposition, as a result of different degrees of professional institutionalization and their relations with the state. This study examines the diversified labor/capital struggle processes on platforms operating at different points of urban mobility in Istanbul and makes an evaluation between delivery and transportation platforms. Therefore, the actions of workers against digital platforms, news reports and public statements of relevant actors in both fields were systematically analyzed. As a result of the study, it is seen that the labor struggle in delivery services includes demands for the regulation of work in parallel with traditional working class reflexes. On the other hand, the resistance in the urban transport platforms is formed in the center of the rent and turns into an institutional struggle as a result of the public activity of the actors. Thus, the inter-class struggle in delivery services operating on digital platforms transforms into an intra-class rent-sharing struggle in urban transport.